Methods for Assessing the Commercial Success of a Computer Game - Yevhen HRABOVSKYI; Katarzyna SZYMCZYK (Communications of International Proceedings, 2021)
The article offers a method of assessing the commercial success of a computer game at the design stage. The characteristics that most influence the success of the game and their parameters are considered. The genres, controls, and popular narrative models of the computer game for each type of player are evaluated. The weights of each characteristic for each player are determined. The consistency of expert assessments was checked on the basis of the ranking method. A formal representation of the success of a computer game has been made. A success score is calculated for each type of player and the percentage of the market segment that will like the game. The scheme of calculation of the estimated number of sold copies of the game is offered. Recommendations for attracting the majority of the audience are formed, which are based on the results of the evaluation of the concept of success for each type of player. The suggested recommendations should be taken into account when creating a promotional video for a computer game.
Keywords: computer game; gaming business; gaming market; evaluation of commercial success; quality of a game.